Geographic variation of Serjania perulacea (Paullinieae, Sapindaceae) and description of two new varieties - Coulleri, Juan Pablo (2017)
We assessed the morphological diversity of Serjania perulacea using multivariate analyses (principal coordinates and component analysis) of quantitative and qualitative morphological leaf traits. We also investigated the effect of local environmental conditions on the distribution of the different phenotypes. Our results indicate that S. perulacea consists of three varieties, which are restricted to specific geographic areas with distinct environmental conditions. The two new varieties S. perulacea var. krapovickasii and S. perulacea var. chacoensis are described here and a lectotype for the autonymic variety is designated. An identification key, illustrations and distribution maps for all three varieties are also provided